2021
DOI: 10.18632/aging.203430
|View full text |Cite
|
Sign up to set email alerts
|

miR-33a-5p inhibits the progression of esophageal cancer through the DKK1-mediated Wnt/β-catenin pathway

Abstract: Esophageal cancer (EC) is one of the most lethal malignancies in humans, and multiple miRNAs have been identified to modulate EC progression by targeting different targets. However, the effect and related mechanism of microRNA-33a-5p (miR-33a-5p) on EC development remain elusive. In this study, we explored the clinical value, function, and possible mechanism of miR-33a-5p in EC. We uncovered that miR-33a-5p and DKK1 are involved in the progression of EC. Significantly, the expression levels of miR-33a-5p were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…However, as the dose response of miR-33a-5p deletion in GC is not clear, it is difficult to determine its corresponding biological response in GC. Many studies have found that miR-33a-5p plays a regulatory role in variety of tumors [12,16]. To explore the miR-33a-5p effect in GC cells, we confirmed the expression, potential targets by QRT-PCR, western blot, and luciferase assay.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, as the dose response of miR-33a-5p deletion in GC is not clear, it is difficult to determine its corresponding biological response in GC. Many studies have found that miR-33a-5p plays a regulatory role in variety of tumors [12,16]. To explore the miR-33a-5p effect in GC cells, we confirmed the expression, potential targets by QRT-PCR, western blot, and luciferase assay.…”
Section: Discussionmentioning
confidence: 76%
“…Many studies have found that miR-33a-5p plays a regulatory role in variety of tumors [ 12 , 16 ]. To explore the miR-33a-5p effect in GC cells, we confirmed the expression, potential targets by QRT-PCR, western blot, and luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, DKK1 was identified as a direct target of miR-372 and miR-373 in breast cancer and CRC cells, and knockdown of DKK1 promoted the growth and invasive activity of cancer cells ( Zhou et al, 2012 ). Many other miRNAs, in addition to the ones mentioned above, have been identified as related to DKK1, including miR-9, miR-31, miR-33a-5p, miR-34a, miR-92b, miR-101, miR-103a-3p, miR-130b-3p, miR-152, miR-291a-3p, miR-302b, miR-373-3p, miR-410, miR-433-3p, miR-488, miR-493, miR-501-5p, miR-522, miR-523-3p, miR-543, miR-590-3p, miR-613, miR-3064-3p, and miR-BART10-3p ( Liu et al, 2016b ; Fan et al, 2016 ; Jia et al, 2016 ; Zhang et al, 2016 ; Feng et al, 2017 ; Lv et al, 2017 ; Tang et al, 2017 ; Weng et al, 2017 ; Wang et al, 2018a ; Wang et al, 2018b ; Chen et al, 2018 ; Zhao et al, 2018 ; Liu et al, 2019 ; Min and Lee, 2019 ; Wang et al, 2019 ; Li et al, 2020a ; Li et al, 2020b ; Liu et al, 2020 ; Xiang et al, 2020 ; Zeng et al, 2020 ; Zhou et al, 2020 ; Liao et al, 2021 ; Song et al, 2021 ; Wu et al, 2021 ).…”
Section: Dkk1 Inhibitorsmentioning
confidence: 99%
“…Relevant studies have shown that miR-128-3p and miR-33a-5p, as tumor suppressor genes, can affect the occurrence, invasion, and metastasis of gastric cancer, esophageal cancer, breast cancer, colorectal cancer, melanomas, and other cancers, through different signaling pathways ( 20 - 23 ). In lung cancer, miR-33a-5p has been reported to inhibit the proliferation and invasion of lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%